Scaffold-free bone-like 3D structure established through osteogenic differentiation from human gingiva-derived stem cells - Masaaki Toyoda; Takao Fukuda; Ryota Fujimoto; Kentaro Kawakami; Chikako Hayashi; Yuki Nakao; Yukari Watanabe; Tsukasa Aoki; Miyu Shida; Terukazu Sanui; Masahide Taguchi; Kensuke Yamamichi; et al. (Biochemistry and Biophysics Reports, 2024)
Introduction & objectives: Stem cell therapy for regenerative medicine has been sincerely investigated, but not still popular although some clinical trials show hopeful results. This therapy is suggested to be a representative candidate such as bone defect due to the accident, iatrogenic resection oncological tumor, congenital disease, and severe periodontitis in oral region. Recently, the Bio-3D printer ''Regenova®'' has been introduced as an innovative three-dimensional culture system, equipped scaffold-free bio-assembling techniques without any biomaterials. Therefore, we expected a mount of bone defect could be repaired by the structure established from this Bio-3D printer using osteogenic potential stem cells. Material & methods: The gingival tissue (1x1 mm) was removed from the distal part of the lower wisdom tooth of the patients who agreed our study. Human Gingival Mesenchymal Stem Cells (hGMSCs) were isolated from this tissue and cultured, since we confirmed the characteristics such as facile isolation and accelerated proliferation, further, strong potential of osteogenic-differentiation. Spheroids were formed using hGMSC in 96-well plates designed for low cell adhesion. The size of the spheroids was measured, and fluorescent immunostaining was employed to verify the expression of stem cell and apoptosis marker, and extracellular matrix. Following four weeks of bone differentiation, μCT imaging was performed. Calcification was confirmed by alizarin red and von Kossa staining. Fluorescent immunostaining was utilized to assess the expression of markers indicative of advanced bone differentiation. Results: We have established and confirmed the spheroids (∼600 μm in diameter) constructed from human GMSCs (hGMSCs) still maintain stem cell potentials and osteogenic differentiation abilities from the results that CD73 and not CD34 were expressed as stem cell positive and negative marker, respectively. These spheroids were pilled up like cylindal shape to the “Kenzan” platform of Bio-3D printer and cultured for 7days. The cylindal structure originated from compound spheroids were tried to differentiate into bone four weeks with osteogenic induction medium. The calcification of bio-3D printed bone-like structures was confirmed by alizarin red and Von Kossa staining. In addition, μCT analysis revealed that the HU (Hounsfield Unit) of the calcified structures was almost identical to that of trabecular bone. Immunofluorescent staining detected osteocalcin expression, a late-stage bone differentiation marker. Conclusion: For the first time, we have achieved the construction of a scaffold-free, bone-like luminal structure through the assembly of spheroids comprised of this hGMSCs. This success is sure to be close to the induction of clinical application against regenerative medicine especially for bone defect disease.